Improving anti-tumor efficacy of low-dose Vincristine in rhabdomyosarcoma via the combination therapy with FOXM1 inhibitor RCM1 - Donovan, Johnny; Deng, Zicheng; Bian, Fenghua; Shukla, Samriddhi; Gomez-Arroyo, Jose; Shi, Donglu; Kalinichenko, Vladimir V.; Kalin, Tanya V. (Frontiers in Oncology, 2023)
Rhabdomyosarcoma (RMS) is a highly metastatic soft-tissue sarcoma that often develops resistance to current therapies, including vincristine. Since the existing treatments have not significantly improved survival, there is a critical need for new therapeutic approaches for RMS patients. FOXM1, a known oncogene, is highly expressed in RMS, and is associated with the worst prognosis in RMS patients. In the present study, we found that the combination treatment with specific FOXM1 inhibitor RCM1 and low doses of vincristine is more effective in increasing apoptosis and decreasing RMS cell proliferation in vitro compared to single drugs alone. Since RCM1 is highly hydrophobic, we developed innovative nanoparticle delivery system containing poly-beta-amino-esters and folic acid (NPFA), which efficiently delivers RCM1 to mouse RMS tumors in vivo. The combination of low doses of vincristine together with intravenous administration of NPFA nanoparticles containing RCM1 effectively reduced RMS tumor volumes, increased tumor cell death and decreased tumor cell proliferation in RMS tumors compared to RCM1 or vincristine alone. The combination therapy was non-toxic as demonstrated by liver metabolic panels using peripheral blood serum. Using RNA-seq of dissected RMS tumors, we identified Chac1 as a uniquely downregulated gene after the combination treatment. Knockdown of Chac1 in RMS cells in vitro recapitulated the effects of the combination therapy. Altogether, combination treatment with low doses of vincristine and nanoparticle delivery of FOXM1 inhibitor RCM1 in a pre-clinical model of RMS has superior anti-tumor effects and decreases CHAC1 while reducing vincristine toxicity.